Properties of the characteristic polynomials and spectrum of Pn and Cn - El Seidy, Essam; Hussein, Salah Eldin; Mohamed, Atef (International Journal of Applied Mathematical Research, 2016)
We consider a finite undirected and connected simple graph Â with vertex set Â and edge set .We calculated the general formulas of the spectra of a cycle graph and path graph. In this discussion we are interested in the adjacency matrix, Laplacian matrix, signless Laplacian matrix, normalized Laplacian matrix, and seidel adjacency matrix.